Patient and treatment factors associated with survival among adult glioblastoma patients: A USA population-based study from 2000–2010. Issue 10 (October 2015) - Pan, I-Wen; Ferguson, Sherise D.; Lam, Sandi
Highlights Our data confirms the survival advantage imparted by marriage in GBM patients. Asians/Hispanics have a significantly lower mortality risk than non-Hispanic whites. Patients in the Northeast have better survival outcomes than in other regions. Patients with supratentorial tumors under 3 cm have better OS than other subgroups. Our data reinforces the positive role of maximal resection in the treatment of GBMs.